Pembangunan Sistem Informasi Pelayanan Laundry Pada RSI Malang "UNISMA" Berbasis Web - Erine Ajeng Pratiwi; Faizatul Amalia; Achmad Arwan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The importance of non-medical services in the fulfillment of facility services at hospitals in addition to health services. Seeing the amount of linen needed in each hospital room by handling it properly. Linen services are carried out to meet the interests of patients in conducting care, so that linen cleanliness needs to be considered with linen laundry. In its application, problems arose including manual recording, incomplete information in the linen laundry service process, and records made again by the head of the household unit for recapitulation. This reduces the sense of satisfaction for the laundry service process and related to the efficiency of time and cost of using books as well as the possibility of major problems that occur because the fulfillment of laundry linen is done every day by officers. Based on the problems that occur the construction of a web-based linen laundry service information system is carried out by applying the waterfall method in system development. Testing is done in four ways, namely unit testing of five samples that were tested using white box testing techniques obtained results of 100% valid status. Validation testing of 42 test cases obtained 100% valid status results. Compatibility testing with system results can run on 11 browsers. Usability testing using the System Usability Scale (SUS) method of 87.5 with excellent and grade scale B categories, which means that the system usability can be accepted.